Heme Oxygenase-1, Oxidation, Inflammation, and Atherosclerosis - Araujo, Jesus A.; Zhang, Min; Yin, Fen (Frontiers in Pharmacology, 2012)
Atherosclerosis is an inflammatory process of the vascular wall characterized by the infiltration of lipids and inflammatory cells. Oxidative modifications of infiltrating low density lipoproteins and induction of oxidative stress play a major role in lipid retention in the vascular wall, uptake by macrophages and generation of foam cells, a hallmark of this disorder. The vasculature has a plethora of protective resources against oxidation and inflammation, many of them regulated by the Nrf2 transcription factor. Heme oxygenase-1 (HO-1) is a Nrf2-regulated gene that plays a critical role in the prevention of vascular inflammation. It is the inducible isoform of heme oxygenase, responsible for the oxidative cleavage of heme groups leading to the generation of biliverdin, carbon monoxide and release of ferrous iron. HO-1 has important antioxidant, antiinflammatory, antiapoptotic, antiproliferative and immunomodulatory effects in vascular cells, most of which play a significant role in the protection against atherogenesis. HO-1 may also be an important feature in macrophage differentiation and polarization to certain subtypes. The biological effects of HO-1 are largely attributable to its enzymatic activity, which can be conceived as a system with three arms of action, corresponding to its three enzymatic byproducts. HO-1 mediated vascular protection may be due to a combination of systemic and vascular local effects. It is usually expressed at low levels but can be highly upregulated in the presence of several proatherogenic stimuli. The HO-1 system is amenable for use in the development of new therapies, some of them currently under experimental and clinical trials. Interestingly, in contrast to the HO-1 antiatherogenic actions, the expression of its transcriptional regulator Nrf2 leads to proatherogenic effects instead. This article reviews the evidence that supports the antiatherogenic role of HO-1, potential pathways and mechanisms mediating those effects.